**Answer:**

Solution:

Step 1: Remove parentheses by multiplying factors.

= (x * x) + (1 * x) + (2 * x) + (2 * 1)

Step 2: Combine like terms by adding coefficients.

(x * x) = x2

(1 * x) = 1x

(2* x) = 2x

Step 3: Combine the constants.

(2 * 1) = 2

Step 4: Therefore, Simplifying Algebraic Expression is solved as

= x2 + 3x + 2.

**Step-by-step explanation:**

1 * -10 is -10 and 1 + (-10) is -9 so the two factors are **1 and -10**

Hope this helps

**Answer:**

The answer for the question is 666

**Step-by-step explanation:**

328+338=666

**1**. 50 * 0.02 = 1. Or 2% of 50 = 1.

Since x is on the right side of the equation, switch the sides so it is on the left side of the equation.<span><span>6<span>x<span>−3</span></span></span>=<span>136</span></span>Create equivalent expressions in the equation that all have equal bases.<span><span>6<span>x<span>−3</span></span></span>=<span>6<span>−2</span></span></span>Since the bases are the same, then two expressions are only equal if the exponents are also equal.<span><span>x<span>−3</span></span>=<span>−2</span></span>Move all terms not containing x to the right side of the equation..Since <span>−3</span> does not contain the variable to solve for, move it to the right side of the equation by adding 3 to both sides.<span>x=<span>3<span>−2</span></span></span>Subtract 2 from 3 to get 1.<span>x=<span>1</span></span>